Case of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) Use in Penetrating Abdominal Aortic Injury - Simon, Meryl A; Russo, Rachel M; Davidson, Anders J; Faulconer, Edwin R; DeSoucy, Erik; Loja, Melissa N; Johnson, M Austin; Williams, Timothy; DuBose, Joseph J; Dawson, David L (Journal of Endovascular Resuscitation and Trauma Management, 2017)
We present the successful utilization of resuscitative endovascular balloon occlusion of the aorta (REBOA) in a case of penetrating abdominal aortic injury. This allowed for hemorrhagic control and exposure of a large aortic defect at the level of the celiac access, which otherwise would have been diffi cult to control in an open fashion. Although use in this specifi c injury pattern in the literature is limited, REBOA can be a life-saving maneuver.